Hubungan Manajemen Laktasi dengan Pemberian Asi Eksklusif pada Bayi Usia 0-6 Bulan di Wilayah Kerja Puskesmas Simpang Tiga Kabupaten Aceh Besar - Ita Kausari; Yadi Putra; Khaira Rizki (Jurnal Sains dan Kesehatan, 2024)
In 2022, the percentage of exclusive breastfeeding in Aceh was in 23rd position or around 65, 88%. This percentage was slightly lower compared to the data in 2021 where the number of exclusive breastfeeding was 66, 66%. This study aims to determine the correlation between lactation management and exclusive breastfeeding for infants aged 0-6 months in Simpang Tiga Public Health Centre. This study is an analytical research design using a cross-sectional approach with a total sample of 49 mothers with babies aged 6-11 months. The sample was chosen by using a total sampling technique. Data collection was gathered by distributing a questionnaire. This study was carried out from July 19th - August 3rd, 2024. The data were analysed using univariate and bivariate analysis with the Chi-Square test. The result shows that of 49 respondents, the majority of the sample were non-exclusive breastfeeding shown by the responses from 28 respondents (57,1%), had middle-class education around 21 respondents (42,9), were unemployed 29 respondents (59,2%), had less knowledge 20 respondents (40,8%), and had no support from most of the families 32 respondents (62,3%). The findings prove a correlation between lactation management and exclusive breastfeeding for infants aged 0–6 months in Simpang Tiga Public Health Centre. This study recommends the respondents increase their knowledge and motivation by exploring information from various sources such as health workers, books, and social media so that mothers will have proper knowledge of exclusive breastfeeding.